Determinants of investment in technology of banks in Vietnam / Liem Nguyen ... [et al.] - Liem, Nguyen; Anh, Vu; Anh, Nguyen; Nguyet, Vo; Tien, Nguyen; Ngoc, Huynh; Thuong, Do (UiTM Press, 2024)
Investment is crucial to economic growth. Technological investment is even more important for a developing economy to keep pace with or even surpass their more advanced peers in shorter periods. The study of the determinants of technological investment in banks in Vietnam was meaningful due to the lack of empirical research and it being a bank-dominated developing economy. Using a sample of 30 commercial banks from 2010 to 2022 in Vietnam, the study investigated the drivers for banks’ investment in technology. The results suggested that banks that are larger tended to invest less, while banks with more equity capital also demonstrated less interest in technological investment. Furthermore, there was some evidence in support of the argument that banks innovate to reduce cost, and that profitable banks tend to be engaged in more innovation. Finally, banks with female CEOs tended to increase investment in technology.